Pengaruh Kualitas Laporan Keuangan dan Sistem Pelaporan terhadap Akuntabilitas Kinerja Keuangan dengan Komitmen Organisasi sebagai Variabel Moderasi : Pada Organisasi Perangkat Daerah Kabupaten Boyolali - Wahyu Nur Eviana; Djoko Kristianto (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of financial statement quality and reporting systems on financial performance accountability with organizational commitment as a moderating variable in Regional Government Organizations (OPD) of Boyolali Regency. This research employs a quantitative approach using primary data obtained through questionnaires distributed to employees involved in financial management within OPD in Boyolali Regency. The sampling technique used purposive sampling with a total of 100 respondents. Data analysis was conducted using SPSS through several testing stages, including instrument quality tests consisting of validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. In addition, the moderating variable was tested using Moderated Regression Analysis (MRA) to determine the role of organizational commitment in strengthening the relationship between the independent variables and financial performance accountability. The results indicate that financial statement quality has a positive and significant effect on financial performance accountability. The reporting system also has a positive and significant effect on financial performance accountability. Furthermore, organizational commitment is proven to strengthen the relationship between financial statement quality and financial performance accountability, as well as strengthen the influence of the reporting system on financial performance accountability. These findings indicate that improving the quality of financial statements, enhancing the effectiveness of reporting systems, and strengthening organizational commitment among government officials are important factors in supporting better financial performance accountability in local government institutions.